Clinical Staging as Prognostic Indicator for Surgical Decision Making Tool in Mammary Tumours in Bitches - Choudhary, Urvashi; Jain, Reshma; Prakash Shukla, Brahm; Singh Parihar, Atul; Deewan Singh Raghuwanshi, Pawan; Shukla, Supriya (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Mammary tumours are the second most common neoplasms in female dogs, following skin tumours and are more prevalent in regions where early spaying is not common. Surgical resection is the gold standard for managing these tumours, providing effective local control, except in cases of inflammatory carcinoma or distant metastases. This study examined the staging and metastases patterns of canine mammary tumours in 25 cases in dogs. Among these 25 animals, 32% were in Stage III, 24% in Stage IV and Stage V, 12% in Stage I and 8% in Stage II. Regional metastases occurred in 10 animals (6 in Stage IV and 4 in Stage V), with thoracic metastases identified in 6 Stage V cases which was confirmed by histopathology of excised tumours. Radiographs showed miliary nodules (<2 mm) in one case and larger pulmonary nodules (>2 mm) in five cases, along with other atypical lesions like pulmonary effusion, cardiomegaly and perihilar nodules. Miliary opacities indicated lymphatic spread, while defined nodules were typical of thoracic metastases. Surgical procedures, including lumpectomy, simple mastectomy and radical mastectomy were chosen based on gross morphology and stage. The dogs with malignant mammary tumours had significantly higher levels of haemoglobin and TLC with neutrophilia, lymphopenia and elevated creatinine compared to those with benign tumours. These findings highlight the need for early detection, accurate staging and personalized surgical intervention to improve prognosis.